2016 Poverty Reduction and Growth Trust : Review of Interest Rate Structure. (Policy Papers; Policy Paper ;, 2016)
This paper reviews the interest rate structure that would apply to the PRGT in 2017-18. Based on the interest rate setting mechanism agreed in 2009, the interest rate for the Extended Credit Facility (ECF) would be zero and the rate for the Standby Credit Facility (SCF) would be 0.25 percent. The interest rate for the Rapid Credit Facility (RCF) was set permanently at zero in July 2015. Since the current mechanism was agreed, the Executive Board has granted successive exceptional interest waivers on all outstanding Fund concessional credit, setting all interest rates charged at zero percent. These waivers have been extended three times, providing interest rate relief to many low-income countries at a time when they faced considerable headwinds from the global economic environment. A strong case remains for maintaining zero rates on Fund concessional credit at the current global economic juncture. The global outlook for LICs has not significantly improved since the last review and downside risks remain significant. At the same time, many Directors noted at the last review in 2014 that the possibility of a prolonged period of very low interest rates warrants an early re-examination of the mechanism, including an exit strategy from repeated application of the waiver, with the objective of safeguarding the self-sustaining capacity of the PRGT. The paper seeks to respond to this call. It proposes that the PRGT interest rate mechanism be amended to accommodate anomalies created by a prolonged period of very low interest rates. Specifically, a new threshold is proposed whereby both the ECF and the SCF rate would be set at zero when the 12-month average SDR rate is less than or equal to 0.75 percent. This proposal will likely keep all PRGT interest rates under the mechanism at zero through at least 2020 given current market expectations while incurring only minimal subsidy costs and eliminating the need for continual waivers. In addition, staff proposes to waive interest rate charges on outstanding legacy balances under the Exogenous Shocks Facility (ESF), which are not determined via the interest rate mechanism, until the next review.